Limites e possibilidades à atuação do direito internacional do meio ambiente na mitigação da poluição plástica marinha - Diógenes, Beatriz Nunes (2020)
Marine plastic pollution represents today one of the major challenges of global environmental governance, being recognized in the international scenario as a contemporary phenomenon of planetary proportions, marked by its cross-border and diffuse nature. In spite of the growing scientific evidence regarding the negative effects of this type of pollution on the marine ecosystem and on human health, there are still a series of conceptual and normative gaps that hinder the adequate treatment of the problem. The methodology used is literature review combined with documentary research. Therefore, the aim of this research is to discern the challenges and possibilities for the action of International Environmental Law (DIMA) in the mitigation of ocean pollution by plastics. To achieve this goal, this work critically discusses the gaps and controversies that revolve around the definition and classification of plastic as “matter” and the absence of a specific legal concept of marine plastic pollution. It questions the incidence of international hard law and soft law instruments, as well as discusses the role of non-state actors in the international agenda. It also discusses the principiological framework of DIMA and presents new perspectives to the sustainable management of plastic materials. Results indicate the need for a more holistic and ecocentric approach, which considers the long-term impacts on future generations and on the ecological integrity of the planet, which articulates different sectors of the international community, including the plastic industry and consumers, especially if thought in terms of Circular Economy. The conclusion point to the importance of remodeling the global governance architecture to address the issue in an appropriate way, the need to adapt the current international normative structure and indicate that it is highly recommended to elaborate a new specific global agreement on the subject.